The role of forensic accounting in combating public sector corruption in Zimbabwe - Munyepwa, Kudakwashe; Ranganayi, Charity; Mudzengerere, Liberty; Mutongereni, Noah; Gwesu, Norah Chishamiso; Machaka, Tafadzwa Hatidani (Goodwood Publishing, 2025)
Purpose: This study investigates how forensic accounting can strengthen public sector accountability and combat corruption in Zimbabwe, a country facing persistent financial irregularities despite existing anti-corruption frameworks. Research methodology: A mixed-methods design was employed, combining qualitative case studies and interviews with forensic auditors and public officials, and quantitative analysis of audit reports and financial misconduct records (2015–2023). Descriptive and inferential statistics (e.g., regression analysis) were used to assess the effectiveness of forensic practices, moderated by internal controls and institutional factors. Results: Findings revealed a significant negative relationship between forensic accounting and fraud incidence (? = -0.58, p < 0.001), and a strong positive association between institutionalized forensic units and financial accountability (? = 0.68, p < 0.001). Integration of forensic and legal mechanisms also enhanced prosecution success rates (? = 0.75, p < 0.001). Qualitative insights confirmed the role of forensic accounting in deterrence, early fraud detection, and evidence-based prosecution. Conclusions: Forensic accounting significantly contributes to improving financial governance, but its effectiveness depends on internal control quality, legal integration, and institutional support. Challenges such as political interference and resource constraints hinder its full potential. Limitations The study is cross-sectional and may be affected by detection bias and reverse causality. Self-reported data and contextual constraints may limit generalizability. Contribution: This is one of the first comprehensive studies linking forensic accounting to anti-corruption outcomes in Zimbabwe, offering theoretical and practical insights for integrating forensic practices into public financial management.